Development of an electrohydraulic drive system for the vibrating conveyor belt of the peanut digger-inverter - Ferezin, Evaldo; Silva, Rouverson Pereira da [UNESP]; Santos, Adao Felipe dos [UNESP]; Zerbato, Cristiano [UNESP] (Public Library Science, 2018)
Hydraulic systems are equipment widely used in stationary industrial equipment and in moving agricultural equipment and construction machines. Currently, the rotation of the vibrating conveyor belt of the peanut digger-inverter is triggered by the tractor power take-off. Considering that for the equipment to operate at its optimal, the tractor engine needs to work at low rotation, responsible for the rotation of the power take-off, this work aimed at developing an electro-hydraulic system able to transmit varying work rotations to the vibrating conveyor belt of the digger-inverter, regardless the rotation of the power take-off and the speed used in the tractor. The electro-hydraulic system uses the oil of the auxiliary hydraulic system (remote control) and electric power of the tractor battery. The rotation of the hydraulic motor that drives the vibrating conveyor axis is controlled by a proportional flow control valve while the direction of rotation is determined by an electro-hydraulic directional valve, controlled by a Vcontrol Personal Device Assistant controller installed in the tractor cab. The electrohydraulic system developed can be used to control the rotation of the vibrating conveyor belt of the peanut digger-inverter since it meets the torque and power requirements necessary to move the vibrating conveyor belt, with the respective rotation control.